2005
DOI: 10.1042/cs20040300
|View full text |Cite
|
Sign up to set email alerts
|

Variation in non-invasive measurements of vascular function in healthy volunteers during daytime

Abstract: Although it is often recommended to standardize the time of day when performing non-invasive measurements of vascular function, the exact influence of the time of day on the outcome of IMT (intima-media thickness), PWV (pulse wave velocity), AIX (augmentation index) and FMD (flow-mediated dilatation) measurements has not been reported before. Nineteen healthy volunteers visited our department on two different occasions: the first visit was at 09:00 hours after an overnight fast, and the second visit was at 14:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 37 publications
(45 reference statements)
5
26
1
Order By: Relevance
“…First, we cannot eliminate the possible diurnal variation in FMD in obese humans, although a diurnal variation seems of little importance for FMD (Etsuda et al 1999;ter Avest et al 2005). When a diurnal eVect on FMD has been shown Fig.…”
Section: Discussionmentioning
confidence: 96%
“…First, we cannot eliminate the possible diurnal variation in FMD in obese humans, although a diurnal variation seems of little importance for FMD (Etsuda et al 1999;ter Avest et al 2005). When a diurnal eVect on FMD has been shown Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Usually, PWV is calculated after arterial pressure waves have been recorded at both a proximal and a distal artery by applanation tonometry: the length of the artery segment between both measurement sites is measured with a tape measure, and the wave transit time ( t) is obtained either by placing a probe on each site and recording the waveforms simultaneously or by recording the waveforms at different sites on separate occasions and using the QRS complex of a simultaneously recorded ECG as a reference frame. Both intra-and inter-observer reproducibility of PWV measurements are reported to be good, regardless of the device used [61,69,72,73]; as for PWA, this could be due to the fact that the technique is relatively simple to learn, even for the inexperienced examiner.…”
Section: Pwvmentioning
confidence: 87%
“…We chose to include time of day in our analysis, but we cannot identify whether the significance of this variable is indicative of diurnal variation, serves as a proxy for temperature, or some combination of these effects (Etsuda et al, 1999). ter Avest et al (2005) found that diurnal variation in vascular function was insignificant if tests were performed during normal working hours under otherwise controlled conditions. No discernable pattern in the coefficient of variation for RHI, by time of day, was observed in our analysis.…”
Section: Study Limitations and Strengthsmentioning
confidence: 98%